QUESTIONS OF PERFECTION OF LEGAL BASE OF PROVIDING OF MUTUAL LEGAL AID ON CRIMINAL CASES - Yerbol Agbayevich Омаров; Baurjan Oitalovich Беремкулов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article presents aspects of legal regulation institution of mutual assistance in criminal matters, and recommendations on improving the legal framework